Model Pertanian Terpadu dalam Mendukung Pertanian Berkelanjutan di Desa Ampukung Kabupaten Tabalong - Riza Adrianoor Saputra; Untung Santoso; Syati Irawati; Ayu Lestari (Universitas Lambung Mangkurat, 2022)
Swampland in Ampukung Village has great potential for the development of an integrated farming model. The area which is dominated by rice cultivation and different land typologies based on the depth of the air allows it to be planted with other agricultural systems. The purpose of this community service activity is to find out the potential of the Ampukung Village area in an effort to implement an integrated farming system in Ampukung Village. The method used to identify the problems and potentials that exist in Ampukung Village is in the form of filling out questionnaires and interviews with 30 farmers. Interviews were conducted with local farmers to understand the techniques and methods that have been carried out so far in farming activities, the weaknesses and problems that exist, as well as forms of local wisdom that live and develop in the community in responding to natural conditions, especially swampland. The results obtained are the potential for implementing an integrated farming system in the form of high interest in doing integrated farming of rice, ducks, and fish in an integrated manner so that three integrated farming models that can be developed are: (1) integrated rice-duck; (2) integrated rice-fish; and (3) integrated duck-fish.